When the Red Light Speaks: Sociotechnical Controversies, Spatial Justice, and Temporal Democracy at the Samsat - Kiaracondong Intersection, Bandung - Farenza Fadil Muhaji; Edit Rahmadhita Anas; Tia Muhamad Reza; Tri Nugroho Putro; Yusran Kahfi Ahmar (Riviera Publishing, 2026)
The Samsat - Kiaracondong (Kircon) intersection in Bandung, Indonesia, reportedly features the longest red-light waiting cycle in the country, reaching peak durations of over 720 seconds. While technocratic discourse frames this signal as a neutral tool for traffic optimization, this article argues that it functions as a contested sociotechnical node where questions of spatial and temporal justice are continuously negotiated. Drawing on Actor-Network Theory (ANT), particularly Latour's concepts of